What Makes a Locality Attractive? Estimates of the Amenity Value of Parks for Victoria1. Issue 3 (9th June 2019) - Evangelio, Roberto; Hone, Simon; Lee, Moses; Prentice, David
Abstract : This paper provides the first estimates of the effects of parks on house prices within Victoria. We estimate hedonic regressions of house prices on the distance to six types of parks as well as a wide range of other amenities that may impact on house prices. We find some types of parks can have substantial positive impacts on house prices, particularly in regional Victoria. The results of this work can be used to construct estimates of the amenity value of a park for a rapid cost‐benefit analysis.